Treatment Outcomes of Laryngeal and Hypopharyngeal Squamous Cell Carcinomas in a Tertiary Care Center of Nepal - Sinha, Pallavi; Sinha, Bimal Kumar; Baskota, Dharma Kanta; Neupane, Yogesh; Acharya, Kunjan (Nepalese Journal of ENT Head and Neck Surgery, 2014)
DOI: http://dx.doi.org/10.3126/njenthns.v3i2.10154 Nepalese Journal of Head and Neck Surgery Vol.3(2) 2012: 10-11